Spiritual Discernment in Decision-Making (Cultura Económica, 2018)
The paper tries to demonstrate that spirituality is not a form of "rational altruism" and the choice of spiritually motivated actors cannot be reduced to the logic of "maximizing an altruistic preference". First, it explains that we need spirituality as a method to solve the socalled "divergent problems" which cannot be solved by the rational calculative mind. Then, it explores the modus operandi of spiritual discernment. Hannah Arendt’s lectures on Kant’s Political Philosophy are a guide in this exploration. Finally, the author gives some indications on how this method of moral judgment and spiritual discernment may renew the foundations of business and leadership.
Keywords: SPIRITUALITY; BUSINESS ETHICS; MANAGEMENT; MORAL JUDGEMENT; LEADERSHIP